2022
DOI: 10.1126/sciadv.abn0900
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced grain boundary facet motion: In situ observations and atomic-scale mechanisms

Abstract: Metals subjected to irradiation environments undergo microstructural evolution and concomitant degradation, yet the nanoscale mechanisms for such evolution remain elusive. Here, we combine in situ heavy ion irradiation, atomic resolution microscopy, and atomistic simulation to elucidate how radiation damage and interfacial defects interplay to control grain boundary (GB) motion. While classical notions of boundary evolution under irradiation rest on simple ideas of curvature-driven motion, the reality is far m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 58 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…However, the termination of grain boundaries at the film-vapor interface, together with the dynamics of the interface itself, dictates both the formation of surface roughness and the overgrowth phenomenon described above. One consequence of the relative immobility of grain boundaries is the emergence of alternating kinks and facets in a subset of grain boundaries [56]. This behavior appears to arise because of the competition between abutting grains with similar, mirrored misorientation, i.e., 0…”
Section: Growth Of the Continuous Filmmentioning
confidence: 99%
“…However, the termination of grain boundaries at the film-vapor interface, together with the dynamics of the interface itself, dictates both the formation of surface roughness and the overgrowth phenomenon described above. One consequence of the relative immobility of grain boundaries is the emergence of alternating kinks and facets in a subset of grain boundaries [56]. This behavior appears to arise because of the competition between abutting grains with similar, mirrored misorientation, i.e., 0…”
Section: Growth Of the Continuous Filmmentioning
confidence: 99%
“…DZs are the microstructural manifestation of highly complex defect-GB interactions. Broadly speaking, these interactions relate the overall GB character, defined by the five-dimensional (5D) space consisting of misorientation and inclination degrees of freedom (dof), with the structure and properties of irradiation defect clusters, although extensive studies in recent times culminating in previously unidentified findings and a much improved understanding of the internal structure of GBs are fast changing this picture (6,(16)(17)(18)(19). In a previous work (20), we have shown that the evolution of the width of the DZ with irradiation dose is associated with changes in GB (internal) microstates.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al were the first to suggest thermal spike diffusion phenomenon [ 50 ]. If the thermal spike occurs on or near a grain boundary, the atoms are thermally activated and can jump across the boundary [ 32 , 57 , 58 , 59 ], resulting in grain boundary migration and thus grain growth.…”
Section: Grain Growth Regimes In Combined Irradiation/thermal Environ...mentioning
confidence: 99%